Aging and Diabetes Increase the Aggregating Potency of Rat Skin Collagen Towards Normal Platelets - Grigorova-Borsos, A M; Bara, L; Aberer, E; Grochulski, A; André, J; Mozère, G; Peyroux, J; Sternberg, M (Thrombosis and Haemostasis, 1988)
Acid-soluble collagen samples were prepared from individual skins of 24 month old rats (n = 8), 2 month old young controls (n = 8) and from 6 month old streptozotocin-diabetic rats (n = 5) and their age-matched controls (n = 10). Less collagen was obtained by acid extraction and salt precipitations from skins of diabetic and aged rats than from those of their respective controls. The collagen preparations from diabetic and aged rats showed an increased ratio of beta/alpha components. The rate of “in vitro” fibrillogenesis was less for collagen from diabetic rats than from controls. It was not modified for collagens from aged rats. The aggregating potency towards normal human platelets was markedly increased for collagens from aged and diabetic rats: reduced latency time (p <0.01) and increased velocity (p <0.01) were observed for collagens from aged rats when compared with young rats (16.5 μg/ml). Increased velocity (p <0.01) was also observed for collagens from diabetic rats (8.25, 11 and 16.5 μg/ ml), without modification of latency time.
Keywords: Skin collagen; Platelet aggregation; Diabetes; Aging